Exploring the Experiences of Pacific Peoples Within Twelve Step Programmes - Nolan, Laura Alexandra Claire (Auckland University of Technology, 2022)
Background: Pacific peoples present with disproportionately higher rates of substance use disorder than the general population, however, are less likely to access mental health and addictions services for support. Despite recent investments into the mental health and addictions sector, uptake of support for Pacific peoples experiencing addictions remains low. The call from Pacific peoples heard throughout the He Ara Oranga Inquiry into Mental Health and Addictions (2018) has been for the adoption of ‘Pacific ways’; promoting Pacific models of health and focusing on healthy relationships, use of Pacific languages and feelings of connectedness. This study aims to explore the experiences of Pacific peoples within Twelve Step Programmes, to ascertain the beneficial and non-beneficial aspects from a Pacific perspective. The findings from this research are intended to inform the development of meaningful interventions for Pacific peoples seeking addictions support. Method: This research project conducted face to face talanoa style interviews with six Pacific peoples who have attended a Twelve Step Programme within the past two years. Interviews were semi-structured and underpinned by the Health Research Council of New Zealand (2014) Pacific Health Research Guidelines. A qualitative research approach was applied using Charmaz’s Constructivist Grounded Theory (2006) methodology alongside Braun and Clarke’s (2006) thematic analysis. Results: Three main themes emerged from the data, which were categorized into a set of subthemes within each primary theme. The first primary theme centred around Pacific peoples lacking knowledge of Twelve Step Programmes. The second theme detailed aspects of Twelve Step Programmes that resonated with Pacific peoples, such as; hospitality and welcoming, spirituality, talanoa, fellowship and connectedness, and volition. The third primary theme explored aspects of Twelve Step Programmes that were non-beneficial for Pacific peoples, which centred around Pacific people being the ethnic minority in Twelve Step Programmes; the need for a Pacific subgroup, and the need for separate spaces for men and women. Conclusion: The recommendations from this research project have been made with the view to enhance and further develop on addictions supports available for Pacific peoples. This research may be of benefit to the alcohol and drug sector; frontline addictions services, mental health and addictions workforce development bodies, Pacific health organisations and policy makers.